Visual hallucination caused by multiloculated hydrocephalus in the frontal lobe: a case report - 石田哲朗 (Brazilian Journal of Case Reports, 2021)
A 72-year-old man consulted our hospital for visual hallucination. His non-contrast computed tomography (CT) of head showed multiloculated hydrocephalus in the frontal lobe. Memantine treatment was started and his visual hallucination disappeared. This is a rare case of frontal lobe damage causing visual hallucination.